Eye on the future : investing in youth now for tomorrow's community (CCS [Georgetown]GY, 2010)
Focuses on the challenges and opportunities for youth in the CARICOM Single Maket and Economy. Makes recommendations to improve their well-being and empowerment.
Keywords: YOUTH